PRINSIF ITIKAD BAIK DALAM SUATU KONTRAK - Warmiyana Zairi Absi; Rusniati Rusniati (Fakultas Hukum Universitas IBA Palembang, 2022)
In civil law the principle of good faith is a rule contained in an agreement, either an agreement between an individual and an individual or an individual with a legal entity. As contained in Article 1338 paragraph (3) of the Civil Code (hereinafter referred to as the Civil Code) it is stated that: